Limits and potentialities to build Past- Present- Future relationships: the imposition of the colonial order in America in textbooks (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2020)
In the framework of the Research Project in the Universidad Nacional de Córdoba the activities present in school manuals are investigated in relation to their limits and possibilities for the formation of historical thought, central category of analysis. The study focuses in particular on one of its dimensions: the historical-temporal consciousness from the construction of past-present-future relationships (human temporality) in the imposition of the colonial order in America. To do this, a comparative key is used with many textbooks used in secondary schools in the province of Córdoba.
Keywords: teaching; textbooks; historical thought